Molecular Mechanisms Underlying Accelerated Aging by Defects in the FGF23-Klotho System - Makoto Kuro-o (International Journal of Nephrology)
The basic research of aging has been primarily focused on elucidating mechanisms of aging and longevity that are evolutionarily conserved from yeasts to primates. Such efforts have culminated in the notion that (1) senescence at the cellular level is associated with aging at the organismal level and that (2) calorie restriction and growth suppression decelerate aging. However, these important findings in the basic research have not necessarily been linked to improvement of daily medical practice in the aging society. It has become increasingly important to investigate mechanisms of aging unique to mammals or humans and apply the research fruits for the treatment of major age-related disorders to extend the health span. Seminal studies on the klotho mouse, a mutant exhibiting a premature aging syndrome, have identified phosphate as a proaging factor in mammals. In this review, mechanisms of phosphate-induced premature aging and potential therapeutic targets will be discussed, which may be directly applicable for developing novel strategies for the treatment of chronic kidney disease and its complications.